Legal Protection Towards Traditional Food Based on Mark and Geographic Indication Law - PURWANINGSIH, Endang; MUSLIKH, MUSLIKH; ANISARIZA, Nelly Ulfah; RAHMANTO, Derta (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
Traditional food makers should be empowered and their products should be protected. The objectives of this research are to identify and analyze the potential, the prospect, and the legal protection of traditional food (producer and products) to finally attain legal protection and trademark or geographic indication. In this research, the method applied is analytical descriptive qualitative by making use of participatory (PRA) and sociological-juridical approaches. The research findings suggest that so far, instead of working on a bigger cause that is achieving mark/label, traditional food producers are still striving for trademark merely to get market distribution and halal label.  It is clear that they need help from related parties considering their economy, sociological humanities (empowerment), and legal aspects (regulation, policy, brand, halal label, consumer protection). Related parties, the Industry and Trade Service,  Cooperatives and SME’s, Directorate General of Property Rights and its regional office, the Department of Agriculture, universities, and the traditional food producers association—should work together and take serious measures to pro-actively involve food makers.